STUDI LITERATUR LATIHAN BERJALAN MENSTABILKAN TEKANAN DARAH PADA HIPERTENSI - Suharto Suharto; Kipa Jundapri; Muchti Yuda Pratama (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
The risk factors of cardivasculer’s diseases it was caused by high blood presure. High blood presure was a factor who caused by hypertention and if blood presure was uncontrolling its caused heart attack and heart failuare. Walking exercise is a submaximal test who recomended for maintenence systolic and dyastolic blood pressure for hypertention. Literature review was collecting from 2010-2019. Data was perfomanced by using CINAHL, Proquest, and Science Direct. The result of this literature review was obtained 30 articles related about walking exercise and hypertention. There was five articles who relevant with this criteria of the study. These articles used quantitative and qualitatif designs. The conclusion was walking exercise can maintenance blood pressure.Keywords: walking exercise, blood presure, systolic dyastolic